2014
DOI: 10.1523/jneurosci.5055-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Medial Prefrontal-Default Mode Network Functional Connectivity in Chronic Pain and Its Association with Pain Rumination

Abstract: Rumination is a form of thought characterized by repetitive focus on discomforting emotions or stimuli. In chronic pain disorders, rumination can impede treatment efficacy. The brain mechanisms underlying rumination about chronic pain are not understood. Interestingly, a link between rumination and functional connectivity (FC) of the brain's default mode network (DMN) has been identified within the context of mood disorders. We, and others, have also found DMN dysfunction in chronic pain populations. The media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
293
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(318 citation statements)
references
References 54 publications
23
293
1
1
Order By: Relevance
“…That is rumination about non-pain related issues may function to inhibit the experience of pain [70]. This possible antinociceptive role for the PCC is consistent with the PCC participating in attentional disengagement from painful experiences during mind wandering [69,73,74]. A proposed mechanism for the PCC participating in antinociception may involve the default mode network circuit (connectivity between the PCC and medial prefrontal cortex) [37] interacting with descending analgesia brain circuits (connectivity between the periaqueductal gray matter and the rostral ventral medulla) [69,74,75].…”
Section: Discussionmentioning
confidence: 53%
“…That is rumination about non-pain related issues may function to inhibit the experience of pain [70]. This possible antinociceptive role for the PCC is consistent with the PCC participating in attentional disengagement from painful experiences during mind wandering [69,73,74]. A proposed mechanism for the PCC participating in antinociception may involve the default mode network circuit (connectivity between the PCC and medial prefrontal cortex) [37] interacting with descending analgesia brain circuits (connectivity between the periaqueductal gray matter and the rostral ventral medulla) [69,74,75].…”
Section: Discussionmentioning
confidence: 53%
“…The resting-state fMRI data were preprocessed using methods and tools previously described in detail (Kucyi et al, 2013(Kucyi et al, , 2014. Using FSL v5.0 (Jenkinson et al, 2012), the fMRI Expert Analysis Tool (FEAT) was used on each subject's fMRI image to remove the first four volumes, extract the brain using the Brain Extract Tool (BET), correct for motion using the Functional MRI of the Brain (FMRIB) Linear Image Restoration Tool (FLIRT) with Motion Correction, and perform linear registration to both subject's T1-weighted anatomical image [six degrees of freedom (DOFs)] and standard MNI152 2 mm space (12 DOFs) using FLIRT.…”
Section: Methodsmentioning
confidence: 99%
“…To interrogate this concept, we examined resting state functional connectivity (FC) and cortical thickness of brain regions implicated in pain perception and its modulation, known as the "pain connectome" (Kucyi and Davis, 2015), in relation to individual differences in temporal summation of pain (TSP). TSP refers to the perception of increasing pain in response to repeated noxious stimuli delivered at a frequency of Ն0.33 Hz, and is the perceptual correlate of "wind-up" in the spinal dorsal horn (Mendell, 1966;Price et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited studies of neurophysiological processes in patients with chronic pain who have high levels of rumination. One study in such patients with temporomandibular disorder demonstrated dysfunction of the default mode network and its interaction with the descending pain modulatory system (28). This neural connectivity change, linking abnormal thought patterns to biological outcomes in the pain pathways, may have significant relevance to FM.…”
Section: Discussionmentioning
confidence: 99%